Genetic divergence and AMMI analysis of hybrid rice (Oryza sativa) in Himalayan foothill regions of Jammu - SINGH, PRAVEEN (The Indian Journal of Agricultural Sciences, 2021)
The present experiment was undertaken during kharif 2017 and 2018 at two locations (Jammu and Kathua) and consisted of nine hybrid rice (Oryza sativa L.) genotypes of diverse origin. The highest grain yield per ha was observed for PAC 807 followed by Sava 200 and PHB 71 based on pooled mean data over the environments. The highest genetic advance were observed for panicle per m2 (9.35), whereas the highest genetic advance as percent of mean was observed for days to flowering (6.15). Genetic divergence study revealed that all the nine hybrid rice genotypes were grouped into three clusters. Cluster II had the largest number of genotypes (5), although they were originated from different sources. Cluster I had three genotypes, whereas cluster III was a single genotype cluster. There was good amount of diversity present in hybrid genotypes with maximum diverse genotypes of PHB 71, BS 008 and BS 1294. Environment III and IV were highly interactive and showed higher mean grain yield for favourable and unfavourable conditions. Environment I (Jammu-2017) showed very less interaction and can be considered as ideal for cultivation of hybrid rice genotypes under study. The hybrid BS 008 and Sava 200 found as a genetically diverse hybrid with stable below average mean performance for grain yield and can be identified as stable genotype under varying conditions of these north western Himalayan foot hill regions of Jammu and Kashmir.